Exploring The Effects Of Entrepreneurship Competency And Environmental Adaptability On Marketing Performance: Business Strategy Mediation In Himki Jepara - Sholikah, Mariatus; Samsul Arifin (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Abstract . This research investigates the influence of entrepreneurial competence and the ability to adapt to the environment on marketing performance in Small and Medium Enterprises (SMEs) in the furniture industry sector in Jepara, by considering the mediating role of business strategy. In the midst of globalization and intense competition, entrepreneurial competence, which includes managerial ability, innovation and risk taking, as well as environmental adaptability, which includes flexibility and response to market changes, have become key factors in improving marketing performance. This research uses a quantitative approach with correlational study methods and Partial Least Squares (PLS) statistical techniques to analyze data from 194 respondents who are members of the Jepara Indonesian Furniture and Crafts Industry Association (HIMKI). The research results show that entrepreneurial competence and environmental adaptability have a positive and significant influence on marketing performance. In addition, business strategy functions as a mediator in the relationship between entrepreneurial competence and marketing performance as well as between environmental adaptability and marketing performance. These findings emphasize the importance of developing entrepreneurial competence and adaptability as factors that not only have a direct impact on marketing performance but also through more effective business strategies. This research provides valuable insights for furniture entrepreneurs in Jepara in optimizing their marketing performance in a dynamic and competitive business environment.